Use Of Social Media By Creative Arts Students For Learning And Creative Artwork Development - Lim, Jing Yi; Balraj Baboo, Shanthi (2016)

(untitled)
Social media is nowadays broadly used by young people. Majority of the young people are with social media sites as it enable them to stay connected with people around the globe anywhere and anytime. The features of social media sites where it allows different forms of content to be shared attract young people's attention and transform ways of communication and interaction between their users. Consequently, majority of higher learning institution are starting to use social media for teaching and learning. This paper explores how the creative arts students are engage in the social media for learning and creative artwork development. Using a mixed methodology, this study used a sample of 300 students from public and private universities and colleges through a questionnaire focusing on the use of social media for learning and creative artwork development specifically in communication and collaboration, information management, learning and problem solving as well as meaningful participation. Discussion sessions are also conducted with 10 students to get better insights. The findings of the study reveal that social media plays a role in getting local and international inputs and feedback for developing creative artwork.